PROBLEMS IN LEARNING JAPANESE LANGUAGE FACED BY STUDENTS - Setiana, Soni Mulyawan; Musyaafa , Muhammad Faiz Khoerul; Setiawati, Linda; Dirgandini, Melinda; Halibanon, Dewi Saparina (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
This research aimed to describe the problems students face while studying Japanese. This research used descriptive analysis methods with a quantitative approach. Data collection was carried out through documentation studies and distributing questionnaires on January 22 - 27 2024 to 43 students of the Communication Science Department of the Universitas Komputer Indonesia, semester V of the 2023/2024 academic year who took Japanese as an elective course. The results showed that most students (81,40%) stated that Japanese was a difficult subject. The problems faced are students’ difficulties in listening, speaking, reading, and writing in Japanese. To overcome this problem, cooperation between lecturers, students, and policymakers to improve the quality of Japanese language learning outcomes is required.